2020
DOI: 10.2147/rmhp.s263155
|View full text |Cite
|
Sign up to set email alerts
|

<p>Behavioural Problems Amongst Pre-School Children in Chongqing, China: Current Situation and Influencing Factors</p>

Abstract: Introduction Behavioural problems in pre-school children are closely related to their mental health. Such problems include attention deficit, personality disorder, overdependency, poor adaptability and conduct problems. Methods From December 2018 to January 2019, we conducted a cross-sectional survey of parents of pre-schoolers. The survey covered sixteen kindergartens in six districts of Chongqing, China. A total of 2200 participants participated in the survey, and 189… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The results of the study indicated that abuse results in negative emotional and behavioral patterns among the subjects. Reinforcing this result, a recent study found that the rate of scolding at home impacts children’s behavioral problems [ 6 ]. Although child abuse is one of the most common types of parental negligence, it has received very little academic attention, especially in developing countries.…”
Section: Theoretical Background and Related Literaturementioning
confidence: 78%
See 2 more Smart Citations
“…The results of the study indicated that abuse results in negative emotional and behavioral patterns among the subjects. Reinforcing this result, a recent study found that the rate of scolding at home impacts children’s behavioral problems [ 6 ]. Although child abuse is one of the most common types of parental negligence, it has received very little academic attention, especially in developing countries.…”
Section: Theoretical Background and Related Literaturementioning
confidence: 78%
“…Several psychological theories attempted to explain the causes and motives behind students’ engagement in abnormal behaviors and suggest ways to measure them, as will be discussed subsequently. Generally, human behavior is divided into normal and abnormal behavior [ 5 ], which may be linked to mental health [ 6 ]. Most people display normal and acceptable behavioral patterns, which reflect their individual’s ability to effectively adapt to their social environment and conform to societal norms.…”
Section: Theoretical Background and Related Literaturementioning
confidence: 99%
See 1 more Smart Citation